THE ROLE OF FOREIGN INDIRECT INVESTMENT IN THE DEVELOPMENT OF IRAQ'S SECURITIES MARKET FOR A WHILE (2009–2021) - M.M. Hawraa Kadhim Jari (American Journals, 2024)
The purpose of the research is to identify the role of foreign indirect investment in the development and strengthening of Iraq ' 's stock market because of its importance in supporting the economy and achieving economic development in developing countries, particularly in developing countries. To achieve the objective of the research, the special indicators of non-Iraqi (rolled shares and value traded) were analysed through the analysis of the traded stock and purchases as well as the value sold and purchases of non-Iraqi stock traded for non-Iraqi stock market for the period 2009 (2021). The searcher adopted the method of analysis of study data. The research came up with important findings: the proportion of the contribution of purchased and sold stock traded in Iraq's stock market during the period of study fell significantly, from the last year of study (12.44%) in 2021 to the last year of study, after it was 37.26% in 2009, at the beginning of the study.
Keywords: Foreign Indirect Investment, Iraq's Securities Market.